Computational constraints on the associative recall of spatial scenes. Issue 5 (10th February 2023) - Ryom, Kwang Il; Stendardi, Debora; Ciaramelli, Elisa; Treves, Alessandro
Abstract: We consider a model of associative storage and retrieval of compositional memories in an extended cortical network. Our model network is comprised of Potts units, which represent patches of cortex, interacting through long‐range connections. The critical assumption is that a memory, for example of a spatial view, is composed of a limited number of items, each of which has a pre‐established representation: storing a new memory only involves acquiring the connections, if novel, among the participating items. The model is shown to have a much lower storage capacity than when it stores simple unitary representations. It is also shown that an input from the hippocampus facilitates associative retrieval. When it is absent, it is advantageous to cue rare rather than frequent items. The implications of these results for emerging trends in empirical research are discussed.